YOUTH VANDALISM IN THE ENVIRONMENT OF MEGALOPOLIS: BORDERS OF STANDARD AND DEVIATION - D. V. Rudenkin; I. V. Vorobyeva; O. V. Kruzhkova; M. S. Krivoshchekova (Obrazovanie i Nauka, 2018)
Introduction. Nowadays, modern urban youth is socialized under entirely different conditions than earlier. Moral relativism of society, diversification of information flows and increasing hedonistic orientations can form a tolerant attitude of young people to many taboo practices, and the specificity of the development of the modern urban environment contributes to the intensification of its vandal behaviour.The aim of the present publication is to identify the understanding of vandalism that is read by modern urban youth and to assess the acceptability of specific vandal practices in the social daily life of young people.Methodology and research methods. The analytical review of scientific works enabled the authors to reconstruct explanatory models of emergence and development of vandalism among young people. The specifics of perception of vandalism of young people were investigated on the basis of a social survey. The data was processed by the methods of correlation and factorial analysis. Statistical calculations were run with application of Population Viability Analysis software – Vortex.Results and scientific novelty. The authors made the complex analysis of the attitude of youth towards vandalism. The dominants of vandalism perception among young people are emphasized. The study was conducted among the representatives of Yekaterinburg (n=304, 18–30 years). It was found that more than 30 % of respondents have a real experience in the implementation of vandalism in the urban environment, but only 2 % of respondents recognize and openly declare this experience. The reason is in the narrowed substantial understanding of vandalism by most of youth representatives; they consider it only as the destructive actions which are not beyond doubt. Moreover, young people do not consider many less obvious offenses as vandalism. Thus, the conclusion is drawn that non-conscious vandalism is widespread among young people: a considerable part of young people more or less regularly commit vandal actions, without perceiving them as a deviation from predefined standard pattern of behaviour; young people do not notice vandal behaviour of people around as well.The data obtained point to considerable flexibility and discrepancy of ideas of vandalism among the young population in megalopolises: vandalism is regarded as deviation and categorically condemned at the level of stereotypes with abstraction from the reality; in a daily occurrence, vandalism is treated as unrecognized norm in relation to specific situations. The tendency of the gradual erosion of taboo nature and deviance of vandalism in consciousness of youth is stated.Practical significance. The materials of the research could be applied to optimize the work on up-brining in educational institutions and to increase the effectiveness of prevention of vandalism among young people.